The Teacher's Reflective Practice Handbook : Becoming an Extended Professional Through Capturing Evidence-informed Practice. - Zwozdiak-Myers, Paula (Taylor & amp, 2012)
What do we mean by reflective practice? What does it involve? How can it help you develop as a teacher? The Teacher's Reflective Practice Handbook is an essential source of advice, guidance and ideas for both student and practising teachers. Helping you to translate pedagogical knowledge into practice, this Handbook guides you through studying your own teaching for personal development, evaluating your lessons through classroom research, and enhancing the quality of pupil learning. It offers an innovative framework which serves to prepare you for the challenges and complexities of the classroo.